Application of the Laws of Defamation and Sedition in Nigeria’s Jurisprudence: Still Relevant? - IYOHA, Odianonsen Francis; OLUJOBI, Olusola Joshua; OYEWUNMI, Olabode A. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The prevalence of defamatory and seditious statements in Nigeria prompts some degree of investigation. These actions typically occur on the platforms of radio, television, public debates, political meetings as well as other public gatherings Moreover, several persons indulge in this illegality under the ‘guise’ of exercising their constitutional right of expression. The objective of this paper is to ascertain the continued relevance of the law of defamation and sedition in Nigeria, coupled with a need to overhaul the legal framework in this respect. Hence, due engagement with mass media organizations and civil society groups provides a veritable mechanism to mitigate incidences of defamation and sedition.